Konsep Kepemimpinan Siyasah Sunni Kontemporer - Ahmad Rizani; Andri Andri; Daaini Rizky Mabrury; Muhammad Rizky Darmawan; Surya Sukti (Indo Publishing, 2026)
This study examines the concept of leadership in contemporary Sunni siyāsah shar'iyyah as a bridge between classical Islamic political thought and modern state systems. Through qualitative analysis of normative sources (Qur'an, hadith, Al-Mawardi) and conceptual developments (Yusuf al-Qaradawi), it explores how principles like ijma', bay'ah, justice ('adl), and shura adapt to democratic governance. Comparative analysis of Pakistan's Islamic federal parliamentary system with Sharia-integrated institutions like the Federal Shariat Court and Indonesia's unitary presidential rechtsstaat with regional autonomy reveals diverse models of religion-state relations post-WWII decolonization. Emerging from weakened colonialism and nationalist movements, these states integrate Islamic legitimacy with modern constitutionalism, demonstrating siyāsah's dynamic relevance for stability, accountability, and human rights in pluralistic societies.